Impact of Synonymous Genome Recoding on the HIV Life Cycle - Jordan-Paiz, Ana; Franco, Sandra; Martínez, Miguel Angel (Frontiers in Microbiology, 2021)
Synonymous mutations within protein coding regions introduce changes in DNA or messenger (m)RNA, without mutating the encoded proteins. Synonymous recoding of virus genomes has facilitated the identification of previously unknown virus biological features. Moreover, large-scale synonymous recoding of the genome of human immunodeficiency virus type 1 (HIV-1) has elucidated new antiviral mechanisms within the innate immune response, and has improved our knowledge of new functional virus genome structures, the relevance of codon usage for the temporal regulation of viral gene expression, and HIV-1 mutational robustness and adaptability. Continuous improvements in our understanding of the impacts of synonymous substitutions on virus phenotype—coupled with the decreased cost of chemically synthesizing DNA and improved methods for assembling DNA fragments—have enhanced our ability to identify potential HIV-1 and host factors and other aspects involved in the infection process. In this review, we address how silent mutagenesis impacts HIV-1 phenotype and replication capacity. We also discuss the general potential of synonymous recoding of the HIV-1 genome to elucidate unknown aspects of the virus life cycle, and to identify new therapeutic targets.